Enhancing nutritional and antioxidant properties of wheat bread: The role of foxtail millet and ripe banana pulp - Md. Jaynal Abedin; Jannatul Tajria; Abu Tareq Mohammad Abdullah; Mohammad Tariqul Hassan; Tasnim Farzana (Food Chemistry Advances)
Bread is primarily made from wheat but can be enriched with dietary fiber and nutrient-rich cereal and plant materials, which are essential for promoting gut health and overall well-being. The study sought to enhance the nutritional profile of wheat bread by including nutrient-dense foxtail millet (FM) and ripe banana pulp (RBP). Five distinct breads were made using various combinations of these ingredients. The inclusion of RBP and foxtail millet flour (FMF) in the bread samples resulted in significantly (p < 0.05) increased amounts of protein (18.92 to 20.92 g/100 g), dietary fiber (13.69 to 18.57 g/100 g), and minerals such as potassium, iron, and zinc. DPPH scavenging activity, total phenolic, flavonoid, and antioxidant content all showed a significant (p < 0.05) increase in overall antioxidant activity after these ingredients were added. The concentration of FMF increased hardness, adhesiveness, and chewiness while decreasing cohesiveness and springiness. The results showed that adding FMF from wheat flour up to a 25 % level could be a useful ingredient, making breads that tasted good and had satisfactory sensory qualities. To summarize, the inclusion of FMF and RBP in regular bread increased nutrient content and phytochemicals, boosting health benefits and reducing food insecurity.